Happy Moves? Assessing the Link Between Life Satisfaction and Emigration Intentions - Artjoms Ivlevs (Institute for the Study of Labor (IZA), 2015)
It has been shown that higher levels of subjective well-being lead to greater work productivity, better physical health and enhanced social skills. Because of these positive externalities, policymakers across the world should be interested in attracting and retaining happy and life-satisfied migrants. This paper studies the link between life satisfaction and one's intentions to move abroad. Using survey data from 35 European and Central Asian countries, I find a U-shaped association between life satisfaction and emigration intentions: it is the most and the least life-satisfied people who are the most likely to express intentions to emigrate. This result is found in countries with different levels of economic development and institutional quality. The instrumental variable results suggest that higher levels of life satisfaction have a positive effect on the probability of reporting intentions to migrate. The findings of this paper raise concerns about possible 'happiness drain' in migrant-sending countries.
Keywords: F22; O15; P2; 330; subjective well-being; life satisfaction; emigration; transition economies